2018
DOI: 10.33182/bc.v8i1.576
|View full text |Cite
|
Sign up to set email alerts
|

DATA-SURVEY: Migrant Acceptance Index: A Global Examination of the Relationship Between Interpersonal Contact and Attitudes toward Migrants

Abstract: Using independently sampled Gallup World Poll survey data from 140 countries, we explored the relationship between interpersonal contact and attitudes toward migrants from a perspective not typically found in the social psychological literature. We hypothesized that respondents who report personally knowing a migrant living in their home country would be more accepting of migrants generally (using a three-item Migrant Acceptance Index (MAI) score) than respondents who do not know a migrant. Results supported o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
5
0
3
Order By: Relevance
“…Will contact with others who threaten and offend us reduce the desire to punish them? Cross-national studies of contact with migrants show promise in that regard ( 46 ), as does nonjudgmental interpersonal conversation ( 47 ). Educating children to respect and empathize with others who are different from them may be an effective antidote to hating and punishing those people later in life.…”
Section: Discussionmentioning
confidence: 99%
“…Will contact with others who threaten and offend us reduce the desire to punish them? Cross-national studies of contact with migrants show promise in that regard ( 46 ), as does nonjudgmental interpersonal conversation ( 47 ). Educating children to respect and empathize with others who are different from them may be an effective antidote to hating and punishing those people later in life.…”
Section: Discussionmentioning
confidence: 99%
“…The Migrant Acceptance Index shows a strong correlation between interpersonal contact with a migrant and the attitudes towards them. Herein, individuals who had previous contact with immigrants have a more positive attitude towards them than do those who did not have such an experience (Fleming et al, 2018).…”
Section: H3: the Fact Of Employing Or Not Employing Immigrants Influementioning
confidence: 99%
“…A wide-ranging survey by Fleming et al, using data from 140 countries, found that in 134 of them such experience improved the perception of immigrants. 17 On the other hand, it is important that the system for receiving migrants should be an orderly one. Feiler has drawn attention to the lamentable consequences of the decision by Chancellor Merkel to open Germany's borders to immigration from the Middle East in 2015, without establishing proper screening and control mechanisms: these consequences included a rise in sexual assault and other violent crime.…”
Section: Refugees As a Special Casementioning
confidence: 99%